Experimental characterization of track ballast under triple-fouling condition: Evidence from selected Nigerian Railways. Issue 1 (1st January 2021) - Bassey, Daniel E.; O. Olukanni, David; Ngene, Ben U.; Bamigboye, Gideon O.
Abstract: This study assessed the aggregate properties that influence track ballast performance along selected Nigerian railway lines. Ballast materials from five selected rail tracks (RT1, RT2, RT3, RT4, and RT5) in Nigeria were collected and assessed in present conditions and after triple-fouling (subjected to degradation, clay, and diesel intrusion). Tests performed include gradation, strength, soundness, and drain-ability tests. Results obtained were compared with the requirements established in five recognized railway ballast standards, where applicable. Initial gradation results indicate that presently, ballast materials from the selected study locations can all be classified as "uniformly graded gravel". However, upon triple-fouling, a gradation shift towards the "well graded" classification was observed. Based on EN 13, 450, the gradations of RT1, RT2, and RT3 ballast materials were more satisfactory than gradations of RT4 and RT5. Strength test results show that ballast materials from tracks RT1, RT2, and RT3 performed satisfactorily based on the five ballast standards considered. RT4 and RT5 on the other hand, only performed suitably based on the AREMA No. 4 ballast standard. The least resistance to weathering was observed in the RT4 and RT5 samples. Initial drain-ability test showed that no ballast sample set achieved the standard drain-ability (3.0 cm/sec). However, RT2 ballast samples indicated the highest drainage capacity with a hydraulic conductivity (k) of 2.285 cm/sec. Furthermore, after triple-fouling, the drainage capacity of all ballast samples largely declined. However, the RT1, RT2, and RT3 samples indicated higher k values compared to RT4 and RT5 ballast samples. Outcomes from the study indicate the need for continuous monitoring of track sub-structure materials along Nigerian railways to ensure its sustainability via improved rail track performance, thereby increasing the safety and efficiency of the Nigerian railway network.